Treatment-Naïve HIV-Infected Patients Have Fewer Gut-Homing β7 Memory CD4 T Cells than Healthy Controls. Issue 11 (November 2017) - Fadul, Nada; Couturier, Jacob; Yu, Xiaoying; Kozinetz, Claudia; Arduino, Roberto; Lewis, Dorothy E.
Abstract : Objectives: The integrin α4β7 is the gut-homing receptor for lymphocytes. It also is an important co-receptor for human immunodeficiency virus (HIV) via glycoprotein (gp)120 binding. Depletion of gut cluster of differentiation (CD)4 T cells is linked to chronic inflammation in patients with HIV; however, measuring CD4 cells in the gut is invasive and not routine. As such, establishing a peripheral marker for CD4 depletion of the gut is needed. We hypothesized that α4β7 CD4 T cells are depleted in the peripheral blood of treatment-naïve patients with HIV compared with healthy controls. Methods: The study groups were treatment-naïve patients with HIV and uninfected controls. Subjects were included if they were 18 years or older with no history of opportunistic infections, active tuberculosis, or cancer. We collected peripheral blood and examined on whole blood using flow cytometry for the following cell surface markers: CD4, CD45RO, chemokine receptor type 5, C-X-C chemokine receptor type 4 (CXCR4), and the integrin β7. We collected demographic information, including age, sex, and ethnicity, as well as viral load (VL) and CD4 count. Two-sample t tests and Fisher exact tests were used to compare the differences between the two groups. Spearman correlation coefficients were calculated between CD4 count and log10 − VL and percentage of CD4 + /CD45RO + /β7 + and log10 − VL in patients. Results: Twenty-two subjects were enrolled in the study (12 patients with HIV and 10 controls). There were no differences in age or sex between the two groups. There were more Hispanics and fewer Asians in the group comprising patients with HIV compared with the control group (7 vs 2 and 0 vs 4, P = 0.05, respectively). Patients infected with HIV had significantly lower frequencies of CD4 + /CD45RO + /β7 + cells (median 12%, range 5–18 compared with uninfected controls: median 20%, range 11–26, P = 0.0007). There was a statistically significant difference in the percentage of CD4 + /CD45RO + /C-X-C chemokine receptor type 4 + cells between patients (72%, range 60%–91%) compared with controls (79%, range 72%–94%, P = 0.04). The percentage of CD4 + /CD45RO + /chemokine receptor type 5 + did not differ between the group of patients with HIV and the control groups (22%, range 11%–57% vs 27%, range 14%–31%; P = 0.8, respectively). There was no correlation between percentage of CD4 + /CD45RO + /β + cells and log10 − VL as measured by the Spearman correlation coefficient ( r = 0.05, P = 0.88) in patients infected with HIV. Conclusions: Memory CD4 β7 + cells are reduced significantly in the peripheral blood of untreated patients infected with HIV, which could be used as a noninvasive indicator of intestinal CD4 T cell loss and recovery. Further studies are needed to examine whether depletion of these CD4 + /CD45RO + /β7 + cells in the peripheral blood parallels depletion in the gut of treatment-naïve patients with HIV and whether levels return to control levels after treatment. Abstract : This study investigates the expression of α4β7, which is the gut-homing receptor for lymphocytes that also is an important co-receptor for human immunodeficiency virus (HIV) via gp120 binding in the peripheral blood of treatment-naïve HIV-infected patients as compared with healthy controls. The authors demonstrated that patients infected with HIV have significantly lower levels of β7-positive CD4 memory T cells in their peripheral blood than healthy controls.